Rigid-resilient transition in calcium borosilicate sealing glass–ceramics: Effect of preferred orientation. Issue 5 (May 2018) - Yan, Jiajia; Chen, Ruiguo; Sa, Baisheng; Lin, Dewei; Hong, Lihua; Xiong, Rui; Wu, Yukun; Chen, Hande; Su, Hongbin; Huang, Qingming; Yang, Hsiwen; Chen, Kongfa; et al.
Abstract: At present, the insufficient thermo-mechanical stability of sealing glass presents a challenge for solid oxide fuel cells (SOFCs). In this work, we report for the first time that a rigid-resilient transition occurs in a calcium borosilicate sealing glass upon heating at 700 °C for different durations. The elastic modulus increases from 28.1–40.0 GPa for 24 h to 92.3–105.1 GPa for 100 h, while the corresponding hardness increases from 2.5–3.1 GPa to 8.1–9.2 GPa. In addition, a possible mechanism for the rigid-resilient transition has been proposed. The reported results provide a new approach to solve the sealing problem of SOFCs.